764 ROCKWOOD CLINICAL FRAILTY SCALE TO PREDICT LENGTH OF STAY, INPATIENT MORTALITY & READMISSION RATE IN A COMMUNITY HOSPITAL SETTING. (8th March 2022) - Daly, D; McSorley, A
Abstract: Introduction: Frailty is prevalent in elderly patients in acute medical wards. It is recognised that length of stay (LOS), inpatient mortality and readmission rates rise with increasing frailty. (Reference: Specialised Clinical Frailty Network: Clinical frailty Scale. 2018. https://www.scfn.org.uk/clinical-frailty-scale ) The Rockwood clinical frailty scale (CFS) is a well-recognised and validated tool, which can be easily incorporated into the comprehensive geriatric assessment to identify the frailest patients and aid in clinical decision making. We collected data on elderly patients in a non-acute community setting to assess the relationship between degree of frailty and outcomes, in this subset of inpatients. Methods: Data was collected on 200 patients admitted to a geriatrician led community hospital over an 8 month period. Patients were all transferred from the affiliated acute hospital site (both medical and surgical wards).Commonest acute diagnoses were: falls, fractures, infections, delirium and heart failure. Premorbid CFS was recorded and patients were divided into 2 groups: CFS ≤ 4: versus CFS ≥5, and outcomes compared to degree of frailty. Results: Of 200 patients, aged ≥65 years, admitted from the acute hospital setting to the community hospital, 28.5% had premorbid CFS ≤4, and 71.5% had premorbid CFS ≥5. Median LOS in the community hospital was 10 days in the less frail group compared to 13 days in the frailer group. One year emergency readmission rate was 58.5% in those with CFS ≤4, and 67% in those with CFS ≥5. Conclusion(s): Accurate recording of premorbid CFS in the non-acute hospital setting can be used to help predict patient outcomes. Used in conjunction with the CGA it is a tool that can aid decision making and prompt discussions with patients and/or families re advance care planning, specifically re suitability of transfer back to the acute hospital setting in the event of a decline in health.